Co4N nanoparticles encapsulated in N-doped carbon framework for boosting electrochemical stability in quantum dot sensitized solar cells. (March 2023) - Li, Wenhua; Zhang, Shule; Guo, Fengye; Yu, Run; Chen, Qianqiao; Zhong, Qin
Abstract: Designing and constructing a delicate structure is an effective strategy to ensure the electrocatalytic stability of catalysts with excellent performance in quantum dot sensitized solar cells (QDSSCs) but remains challenging. Herein, ultrafine Co4 N nanoparticles are encapsulated in a fish-scale-like N-doped carbon framework (Co4 N@NC) in the form of Co–N–C bonds via a facile three-step method, including precursor construction, calcined carbonization and nitridation process. Notably, in the exquisite precursor construction process, the gelatinous chitosan induced by citric acid effectively bonds Co(Ⅱ) ions, and a fish-scale-like structure is designed under the action of template F127. The construction of this composite structure can increase contact with the electrolyte, favor electron conduction between particles, and improve the stability of the catalyst, thereby dramatically boosting the polysulfide reduction performance for QDSSCs. Co4 N@NC is employed as the counter electrode (CE) of QDSSCs for the first time, its charge transfer resistance ( R ct ) is as low as 1.12Ω, and the power conversion efficiency of CdS/CdSe QDSSC reaches 5.54%, confirming extraordinary reduction activity towards Sn 2− . Especially, compared with Co4 N CE, Co4 N@NC CE has better tolerance to polysulfide electrolytes and shows excellent electrochemical stability. This work provides a new strategy to improve the performance and stability of Co4 N for the polysulfide reduction reaction. Graphical abstract: Image 1 Highlights: An enlightened route is provided to design metal nitride/N-doped carbon composites. Fish-scale-like morphology promotes electron transfer between the layers. N-doped carbon as an encapsulated matrix improves electrocatalytic stability. The prepared Co4 N@NC exhibits efficient and stable polysulfide reduction activity. CdS/CdSe QDSSC based on Co4 N@NC CE exhibits a superior PCE of 5.54%.